Effect of azithromycin on bronchiolitis obliterans syndrome in posttransplant recipients: A systematic review and meta-analysis. Issue 28 (15th July 2022) - Hao, Xiaohui; Peng, Cheng; Lian, Wenwen; Liu, Han; Fu, Guiying
Abstract : Background: Bronchiolitis obliterans syndrome (BOS) is a devastating complication that occurs after transplantation. Although azithromycin is currently used for the treatment of BOS, the evidence is sparse and controversial. The aim of this meta-analysis is to evaluate the effects of azithromycin on forced expiratory volume in 1 second (FEV1 ) and patient's survival. Methods: PubMed, Embase, Cochrane library, Web of Science databases, and the ClinicalTrials.gov registry were systematically searched from inception until December 2020 for relevant original research articles. Random-effects models were used to calculate pooled-effect estimates. Results: Searches identified 15 eligible studies involving 694 participants. For FEV1 (L), there was a significant increase after short-term (≤12 weeks; P = .00) and mid-term (12–24 weeks; P = .01) administration of azithromycin. For FEV1 (%) compared to baseline, there was a significant increase after short-term (≤12 weeks) administration of azithromycin ( P = .02), while there were no statistically significant differences in the medium and long term. When pooled FEV1 % was predicted, it exhibited a similar trend to FEV1 (%) compared to baseline. In addition, we discovered that azithromycin reduced the risk of death (hazard ratio = 0.26; 95% confidence interval = 0.17 to 0.40; P = .00) in patients with BOS post–lung transplantation. Conclusions: Azithromycin therapy is both effective and safe for lung function improvement in patients with posttransplant BOS after the short- and medium-term administration. Additionally, it has been demonstrated a significant survival benefit among patients with BOS post–lung transplant. Higher quality randomized controlled trials and more extensive prospective cohort studies are needed to confirm the effect of azithromycin on patients with posttransplant BOS.